PERANAN KEPEMIMPINAN CAMAT DALAM IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI DI KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - MAWU, VALLEN REZA PRATAMA; OGOTAN, MARTHA; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACTThe chief of a district as district leader is either one perpetrators of PNPM Mandiri in thedistrict as a founder execution PNPM Mandiri to the villages in the district area. That iswhy the role district leadership on the implementation PNPM Mandiri in the district to bevery important and to determine. In connection with that’s thing then this researchintended to answer the question how the role of district leadership on the implementationPNPM Mandiri in the Pasan District Southeast Minahasa Regency.Based on literature review then the role of district leadership on the implementationPNPM Mandiri viewed from three activity the chief of a district as a founder executionPNPM Mandiri in the district are the role to socialize program with build and direct theperpetrators PNPM Mandiri in the district and village; the role of coordinate plan andexecution a program PNPM Mandiri in the villages; and the role to control execution aprogram PNPM Mandiri in the villages.This research used qualitative method. Data source/informant take from theperpetrators unsure PNPM Mandiri in the district level and in the village level, are 14peoples. Data collection used interview technique. Whereas data analyze used techniquequalitative analyze interactive mode by Miles and Hubernan.The result of the research to showed : (1) the chief of a district’s role to socialize aprogram with build and direct the perpetrators PNPM Mandiri in the district level andvillages in the Pasan District area can be performed effectively; (2) the chief of a district’srole to coordinate plan and execution a program PNPM Mandiri in the villages in thePasan District area can be performed effectively; (3) the chief of a district’s role to controlexecution a program PNPM Mandiri in the villages in the Pasan District area can beperformed effectively.Based on the result of that research deduced role of the chief of a district’sleadership on the implementation PNPM Mandiri in the district already can be realized byeffective in the Pasan District Southeast Minahasa.Based on the result of this research then suggested that the chief of a district’sleadership on the implementation PNPM Mandiri in the Pasan District still needs to beimproved so it becomes more effective.Keywords : the chief of a district’s leadership, implementation PNPM Mandiri